Assessment of Factors Influencing Consumer Green Purchase Intentions Towards Home Appliance Products in Indonesia Using the Extended Theory of Planned Behavior - Hardian Reza Dharmayanda; Nurdin Sobari (Green Publisher Indonesia, 2024)
Indonesia is experiencing significant economic growth, increasing consumer demand for home appliances, but it impacts the environment. Thus, manufacturers, regulators, and marketers need valuable insights into understanding how to effectively target environmentally conscious consumers in Indonesia. This study aims to establish a comprehensive framework utilizing the Extended Theory of Planned Behavior (TPB) to assess the determinants influencing Indonesian consumers' purchase intentions toward environmentally friendly home appliance products in Indonesia. The research analyzes the impact of eco-innovation, green products, environmental concerns, knowledge, and perceived value and risks associated with green products. This study adopts an empirical research design and gathers data using a quantitative methodology via survey questionnaires from 280 respondents. The robustness of the research is further enhanced by using structural Equation Modeling (SEM) to validate the proposed research framework and test various hypotheses concerning the relationships between the identified factors and green purchase intentions. This section will summarize the key results of the research, such as the most significant determinants of purchase intentions and the strength of the mediating effects between green trust and consumer attitude. This indicates that several variables, such as environmental concern, eco-innovation, and green perceived value, have contrasting results from preliminary assumptions based on references. Also, attitude is important as a mediating variable rather than green trust to influence consumer purchase intentions toward green home appliance products.